2020
DOI: 10.1093/mnras/staa3796
|View full text |Cite
|
Sign up to set email alerts
|

Polarized kilonovae from black hole–neutron star mergers

Abstract: We predict linear polarization for a radioactively powered kilonova following the merger of a black hole and a neutron star. Specifically, we perform 3D Monte Carlo radiative transfer simulations for two different models, both featuring a lanthanide-rich dynamical ejecta component from numerical-relativity simulations while only one including an additional lanthanide-free disc-wind component. We calculate polarization spectra for nine different orientations at 1.5, 2.5, and 3.5 d after the merger and in the $0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 71 publications
0
22
1
Order By: Relevance
“…Because the expansion occurs rapidly due to the high velocity, the emission from the dynamical ejecta is likely to be observed directly irrespective of the disk outflow. The polarization degree of $ 1% for the wavelength of J0:7lm might still be expected in a wide range of the viewing angle at 1-2 d after merger for a combination of ejecta components (Bulla et al 2021, see also Li and Shen 2019 for an early-time polarization with hypothetical existence of free neutrons).…”
Section: Kilonova/macronovamentioning
confidence: 94%
See 2 more Smart Citations
“…Because the expansion occurs rapidly due to the high velocity, the emission from the dynamical ejecta is likely to be observed directly irrespective of the disk outflow. The polarization degree of $ 1% for the wavelength of J0:7lm might still be expected in a wide range of the viewing angle at 1-2 d after merger for a combination of ejecta components (Bulla et al 2021, see also Li and Shen 2019 for an early-time polarization with hypothetical existence of free neutrons).…”
Section: Kilonova/macronovamentioning
confidence: 94%
“…Furthermore, simulations with weak interactions including neutrino-radiation transfer give us the distributions of thermodynamic quantities such as the electron fraction in the ejecta, which determine the nucleosynthetic yield and hence microscopic properties (iii) and (iv). Precise multiband light curves have been calculated by photon-radiation-transfer simulations based on the ejecta properties derived by numerical-relativity simulations of black hole-neutron star binaries (Tanaka et al 2014;Ferna ´ndez et al 2017;Kawaguchi et al 2020b;Bulla et al 2021;Darbha et al 2021). In the following, we briefly review current understanding of the kilonova/macronova with particular emphasis on features specific to black hole-neutron star binaries.…”
Section: Kilonova/macronovamentioning
confidence: 99%
See 1 more Smart Citation
“…KNe accompanying BH-NS mergers might be better targets in this respect since the ejecta distribution is more strongly asymmetric compared to the BNS case. Indeed, Bulla et al [157] found that polarization levels up to 6 % may be achieved in these system for favourable viewing angles and when observing at near-IR wavelengths ( 1µm).…”
Section: Constraints From Kilonova Polarimetrymentioning
confidence: 99%
“…This model was later used by Breschi et al (2021) to perform a joint electromagnetic, gravitational wave parameter estimation for GW170817. More advanced models use multi-frequency Monte Carlo radiative transfer calculations (Kasen et al 2013;Wollaeger et al 2018;Kawaguchi et al 2018;Korobkin et al 2021;Bulla et al 2021). Surrogate models that can interpolate detailed Monte Carlo calculations have also been proposed (Coughlin et al 2018).…”
mentioning
confidence: 99%